1995
DOI: 10.1099/0022-1317-76-11-2679
|View full text |Cite
|
Sign up to set email alerts
|

PU box-binding transcription factors and a POU domain protein cooperate in the Epstein--Barr virus (EBV) nuclear antigen 2-induced transactivation of the EBV latent membrane protein 1 promoter

Abstract: Expression of the Epstein-Ban" virus (EBV) latent membrane protein (LMP1) is regulated by virus-and host cell-specific factors. The EBV nuclear antigen 2 (EBNA2) has been shown to transactivate a number of viral and cellular gene promoters including the promoter for the LMP1 gene. EBNA2 is targeted to at least some of these promoters by interacting with a cellular DNA binding protein, RBP-Jlc. In the present report we confirm and extend our previous observation that the LMP1 promoter can be activated by EBNA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 54 publications
(43 reference statements)
3
84
0
Order By: Relevance
“…Downregulation of RTA-mediated transactivation by TLE2 could be an important mechanism by which the host cell responds to the microenvironmental stimuli that potentially reactivate the virus through preventing expression of viral genes and suppressing viral DNA replication during coevolution of virus and host. This is supported by recent studies on EpsteinBarr virus, another human herpesvirus, which have demonstrated that the corepressor Groucho/TLE can repress EBNA1 (Epstein-Barr virus nuclear antigen 1) auto-activation and interfere with latent infection by cooperation with Oct-1 (60).…”
Section: Discussionsupporting
confidence: 58%
“…Downregulation of RTA-mediated transactivation by TLE2 could be an important mechanism by which the host cell responds to the microenvironmental stimuli that potentially reactivate the virus through preventing expression of viral genes and suppressing viral DNA replication during coevolution of virus and host. This is supported by recent studies on EpsteinBarr virus, another human herpesvirus, which have demonstrated that the corepressor Groucho/TLE can repress EBNA1 (Epstein-Barr virus nuclear antigen 1) auto-activation and interfere with latent infection by cooperation with Oct-1 (60).…”
Section: Discussionsupporting
confidence: 58%
“…Having two control regions also allows tissue-specific or signal transduction-specific expression after establishment of infection. LMP1 is also expressed from two promoters that are responsive to completely different transcription factors (6,9,23,35,46,50,51,59).…”
Section: Discussionmentioning
confidence: 99%
“…EBNA-2 activates transcription of cellular genes, including CD21, CD23, and c-myc and of viral genes, including the EBNAs, LMP1, and LMP2 (1,2,8,17,32,60,(69)(70)(71). EBNA-2 has the intrinsic ability to self associate and recognizes promoters by binding to RBP-J and PU.1/Spi1, cellular transcription factors that recognize specific DNA sequences (20,25,26,31,58). Once associated with a promoter, the EBNA-2 acidic domain can recruit basal and activated transcription factors p300, CBP, and PCAF histone acetylases and a p100 transcriptional coactivator (25,(65)(66)(67)73).…”
Section: Ha95 a Nuclear Protein Homologous To Akap95 Has Been Identmentioning
confidence: 99%